Characteristics, microorganism, and antibiotic profile of patients with Fournier’s gangrene in a tertiary care centre in Indonesia: A retrospective analysis of 43 cases - Jeremy Thompson Ginting; Gampo Alam Irdam (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Background: Fournier’s gangrene (FG) is a fatal condition that often leads to death if not treated properly. To this date, there are no data regarding FG in Indonesia. Objective: This study aims to investigate the characteristics of patients with FG.Methods: A cross-sectional study design was used to evaluate the medical records of patients admitted to Cipto Mangunkusumo Hospital between January 2012 and December 2017.Results: The median age of the subjects were 51 (2-81) years. All of the subjects were male and presented with scrotal pain. The scrotal abscess was found in 38 (88.4%) cases. Type II diabetes was found in 10 (23.3%) subjects. E. coli was the most dominant causative agent in 28 (65.1%) cases. Meropenem was administered in 16 (37.2%) subjects, and 16 (37.2%) subjects had antibiotics administered for ≤7 days. Conclusion: Although the mortality rate has decreased, those with FG tend to have a long hospital stay, which implies a high risk of complications. All males presenting with scrotal pain should be suspected of FG. Further studies on long-term hospitalisation complications in those with FG are required.